Covid-19 and Traveling Intention: A Risk Perception - Rifqi Amrulloh; Firda Nosita (Budapest International Research and Critics University, 2022)
The new virus outbreak namely SARS-Cov-2 was first discovered in Wuhan, China, and became a pandemic because it spread rapidly to various countries in 2020. The Covid-19 pandemic has an impact on various community activities, such as traveling. The purpose of this research is to find out public knowledge about Covid-19 risks and the effect of the Covid-19 pandemic on their travel plans. The survey was conducted by asking questions about travel plans and learning about the Covid-19 pandemic. The survey was collected using a google form, which was distributed through various social media with a sample of 570 respondents spread from different regions in Indonesia. The survey results show that the majority of respondents have known about the Covid-19 outbreak since December 2019, know the countries affected, and know the characteristics of people infected with Covid-19. As many as 67.4% of respondents stated that they had plans to travel in 2020, but the majority of them decided to postpone or cancel their travel plans. Respondents strongly agree that Covid-19 is highly contagious, deadly, and consider traveling during a pandemic very risky. However, respondents strongly believe that the Covid-19 pandemic will end soon in 2020. The results of this survey prove that health risks are a crucial factor for people in making travel decisions.